Rubus rosifolius (Rosaceae) stem extract induces cell injury and apoptosis in human hepatoma cell line - De Quadros, Ana Paula Oliveira [UNESP]; Oshiiwa, Bruna [UNESP]; Petreanu, Marcel; Niero, Rivaldo; Rosa, Paulo Cesar Pires; Sawaya, Alexandra Christine Helena Frankland; Mantovani, Mario Sergio; O'Neill De Mascarenhas Gaivão, Isabel; Maistro, Edson Luis [UNESP] (Elsevier, 2023)
Rubus rosifolius, popularly known as “red mulberry”, is a common medicinal plant in southern Brazil and is used as an antidiarrheal, analgesic, antimicrobial and antihypertensive, and to treat stomach diseases. The aim of this study was to analyze the R. rosifolius stem extract (RrSE) for possible in vitro cytotoxic and genotoxic effects, using the comet assay and the micronucleus test to assess genotoxicity, and flow cytometry to assess the impact on the cell cycle and apoptosis in HepG2/C3A cells, in addition to evaluating the expression of genes linked to the induction of DNA damage, cell cycle, apoptosis and metabolism of xenobiotics. The MTT assay observed no cytotoxic effects at concentrations between 0.01 and 100 μg/mL of the extract. However, genotoxic effects occurred in treatments with the extract from a 1 μg/mL concentration. Flow cytometry analysis revealed a significant increase in cells in the G2/M phase after treatment with 10 μg/mL, a decrease in cells in the G0/G1 phase in the treatment with 100 μg/mL, and a significant increase in total apoptotic cells. In the gene expression analysis, an increase in the CYP1A2 xenobiotics metabolizing gene expression was observed. Despite the promising pharmacological effects of R. rosifolius, the results revealed that the RrSE has genotoxic effect and induces apoptosis in HepG2/C3A cells, indicating danger in using this plant extract by humans.
Keywords: Apoptosis analysis; Cell cycle analysis; Comet assay; Gene expression; Micronucleus test; Rubus rosifolius toxicity